HUBUNGAN KOMUNIKASI EFEKTIF MENGGUNAKAN TEKNIK SBAR DENGAN INSIDEN KESELAMATAN PASIEN DI RUANG COVID-19 RS X - Rifki Anugerah (2022)
Patient safety is a system that implements a patient care system that is safer and can reduce injuries caused by mistakes in actions that have been carried out by nurses and their colleagues. One component of patient safety goals is effective communication. Communication in medical services is very important because it aims to improve complete service to patients to ensure their safety. This study aims to identify the effect of SBAR communication on patient safety incidents in X Hospital. This research is using descriptive analytic research design with cross sectional approach. The sampling technique used is a total sampling of 45 people. The results of the study using the Chi Square test showed that there was a significant effect between SBAR communication and patient safety incidents with a p value of 0.026 (OR) = 4,000. The conclusion of this study is that nurses have poor communication in reducing the occurrence of patient safety incidents. Nurses are expected to be able to improve effective communication skills and increase knowledge related to patient safety goals in order to reduce the number of patient safety incidents.